Direct Election Of Regional Heads By The People From A Utilitarian Perspective - Krida Kurina Jaya; Hari Wiyanto; Marsudi Dedi Putra (JURNAL HUKUM SEHASEN, 2024)
This research aims to analyze the direct election of regional heads by the people in the context of utilitarianism theory. This direct election is an integral part of the modern democratic system in many countries, including Indonesia, which gives citizens, especially regional communities, direct voting rights to elect their own regional leaders. However, in the perspective of utilitarianism, political decisions and government actions are measured based on their consequences or impact on the happiness and welfare of society as a whole. Therefore, this research will explore the extent to which a direct regional head election system can be justified from a utilitarianism perspective, taking into account the effectiveness of elected leaders, political participation, and their impact on social and economic justice. Through in-depth analysis, it is hoped that this research can provide deeper insight into the relationship between the direct election of regional heads by the people and the principles of utilitarianism, as well as their implications for the practice of democracy and regional government governance in Indonesia. The results of this research can also provide a valuable contribution in developing more effective and fair policies in the regional head election system, in accordance with the principles of utilitarianism in achieving the welfare of society as a whole.